Comparison of outcomes after differentiated thyroid cancer surgery performed with and without energy devices: A population-based cohort study using a nationwide database in Japan. (May 2020) - Konishi, Takaaki; Fujiogi, Michimasa; Niwa, Takayoshi; Morita, Kojiro; Matsui, Hiroki; Fushimi, Kiyohide; Tanabe, Masahiko; Seto, Yasuyuki; Yasunaga, Hideo
Abstract: Background: The benefits of using energy devices (EDs) such as ultrasonic coagulating shears or electrothermal bipolar vessel sealing devices for thyroid cancer surgery have been evaluated only with limited data obtained from small samples. Materials and methods: Using a Japanese national inpatient database, we identified 59, 394 patients with thyroid cancer who underwent thyroidectomy without EDs (without-ED group, n = 32, 360) and with EDs (with-ED group, n = 26, 764) from July 2010 to March 2017. One-to-one propensity score matching was performed to compare the occurrence of postoperative complications including recurrent laryngeal nerve paralysis and chyle leakage, duration of anesthesia, length of stay, total costs, in-hospital mortality rate between the two groups. We also performed multivariate regression analyses using a generalized estimating equation and multiple imputation as a sensitivity analysis. Results: In the propensity-matched analysis involving 22, 108 pairs, no significant differences were found in any postoperative complications (7.4% vs. 7.3%, p = 0.73), duration of anesthesia (217 min vs. 218 min, p = 0.54), length of stay (8.7 days vs. 8.2 days, p = 0.07) and in-hospital mortality rate (0.07% vs. 0.09%, p = 0.61). Compared with the without-ED group, the with-ED group showed a lower occurrence of postoperative recurrent laryngeal nerve paralysis (2.3% vs. 2.7%, p = 0.01) but a higher occurrence of postoperative chyle leakage (0.3% vs. 0.1%, p < 0.001) and total cost (US 7246 vs. US 6937, p < 0.001). The multivariate regression analysis showed compatible results with the propensity-matched analysis. Conclusion: In this large nationwide cohort of patients with thyroid cancer, no significant difference was detected in the proportions of any complications. The use of EDs was associated with a lower occurrence of postoperative recurrent laryngeal nerve paralysis but a higher occurrence of postoperative chylothorax and higher cost. Highlights: Energy device use in thyroid cancer surgery was associated with lower occurrence of recurrent laryngeal nerve paralysis. Energy device use was, however, associated with higher occurrence of postoperative chyle leak and higher costs. Energy device use did not have significant advantages in any complications, duration of anesthesia and length of stay.